Community effectiveness of copepods for dengue vector control: systematic review1. Issue 6 (22nd March 2015) - Lazaro, A.; Han, W. W.; Manrique‐Saide, P.; George, L.; Velayudhan, R.; Toledo, J.; Runge Ranzinger, S.; Horstick, O.
Abstract Objective Vector control remains the only available method for primary prevention of dengue. Several interventions exist for dengue vector control, with limited evidence of their efficacy and community effectiveness. This systematic review compiles and analyses the existing global evidence for community effectiveness of copepods for dengue vector control. Methods The systematic review follows the PRISMA statement, searching six relevant databases. Applying all inclusion and exclusion criteria, 11 articles were included. Results There is evidence that cyclopoid copepods (Mesocyclops spp.) could potentially be an effective vector control option, as shown in five community effectiveness studies in Vietnam. This includes long‐term effectiveness for larval and adult control of Ae. aegypti, as well as dengue incidence. However, this success has so far not been replicated elsewhere (six studies, three community effectiveness studies – Costa Rica, Mexico and USA, and three studies analysing both efficacy and community effectiveness – Honduras, Laos and USA), probably due to community participation, environmental and/or biological factors. Judging by the quality of existing studies, there is a lack of good study design, data quality and appropriate statistics. Conclusion There is limited evidence for the use of cyclopoid copepods as a single intervention. There are very few studies, and more are needed in other communities and environments. Clear best practice guidelines for the methodology of entomological studies should be developed.